Outcomes of direct-acting antivirals in patients with HCV decompensated cirrhosis: a systematic review and meta-analysis - Jongraksak, Tanawat; Chuncharunee, Alan; Intaraprasong, Pongphob; Tansawet, Amarit; Thakkinstian, Ammarin; Sobhonslidsuk, Abhasnee (Frontiers in Medicine, 2023)
Background Direct-acting antivirals (DAA) are effective for chronic hepatitis C virus (HCV) treatment. However, their impact on overall survival (OS), hepatocellular carcinoma (HCC) occurrence, HCC-free survival, and liver function in patients with HCV decompensated cirrhosis remains uncertain. This study aimed to evaluate the effects of DAA treatment on this population. Methods Studies were identified by searching the MEDLINE, SCOPUS, and CENTRAL databases. OS and HCC-free survival probabilities and time data were extracted from Kaplan-Meier curves. A one-stage meta-analysis using parametric Weibull regression was conducted to estimate the relative treatment effects of DAA vs. no DAA. The primary outcome was the OS rate. The secondary outcomes were HCC-free survival, HCC occurrence rate, and improvement in the Model for End-stage Liver Disease (MELD) score. Results Eight cohorts comprising 3,430 participants (2,603 in the DAA group and 1,999 in the no-DAA group) were included. The OS probabilities at 12 and 24 months were 95 and 90% for the DAA group, respectively, compared with 89 and 80% in the no-DAA group, respectively. Hazard ratio (HR) was 0.48 (95% confidence interval (CI): 0.39, 0.60; p < 0.001). The HCC-free survival probabilities at 12 and 24 months were 96 and 90%, respectively, in the former, and 94 and 85%, respectively, in the latter. The HR of HCC occurrence was 0.72 (95% CI: 0.52, 1.00; p = 0.05), which suggests that DAA treatment in decompensated cirrhosis may lead to a 28% lower risk of HCC occurrence. The mean MELD score difference was −7.75 (95% CI: −14.52, −0.98; p = 0.02). Conclusion Improvement in OS and MELD score is a long-term benefit of DAA treatment in patients with HCV decompensated cirrhosis, with a marginal effect of the treatment on HCC development.